Emotion recognition from body movement and gesture in children with Autism Spectrum Disorder is improved by situational cues. (March 2019) - Metcalfe, Dale; McKenzie, Karen; McCarty, Kristofor; Pollet, Thomas V.
Highlights: CGI gesture and posture stimuli, devoid of facial expressions, conveyed emotions. Supports previous findings of poorer emotion recognition in people with ASD. Situational cues aid both people with and without ASD correctly identify emotions. Abstract: Background: Research shows people with Autism Spectrum Disorder (ASD) have poorer emotion recognition (ER) compared to their typically developing (TD) peers. However, it is not known whether this is the case when stimuli are limited to gesture and posture, and lack facial expressions. Method: Fifty-four children with ( n = 27) and without ( n = 27) ASD, matched on age and gender, completed an ER task, that used dynamic stimuli. Processing style bias, Autistic-like-traits and empathy were also measured. With ER as the outcome variable, a multilevel logistic model was created. Results: Children with ASD were found to be significantly less accurate in identifying emotions, compared to the control group. Presence of situational cues aided both groups. Autistic-like-traits and empathy were found to correlate too highly with the diagnosed condition to use in the multilevel model. Processing style did not significantly impact ER ability. Conclusions: This study supports previous research which finds ER ability in people with ASD to be poorer than that of TD peers and that situational cues can aid ER ability. Importantly, the latter is true for people with ASD. The implication of these findings are programmes that aim to improve ER should consider using cues. Limitations of the study are discussed.